The Unexplored Socio-Cultural Benefits of Coffee Plants: Implications for the Sustainable Management of Ethiopia’s Coffee Forests - Bulitta, B.J.; Duguma, L.A. (MDPI, 2021)
Coffee is among the most popular commodity crops around the globe and supports the livelihoods of millions of households along its value chain. Historically, the broader understanding of the roles of coffee has been limited to its commercial value, which largely is derived from coffee, the drink. This study, using in-depth interviews and focus group discussions, explores some of the unrevealed socio-cultural services of coffee of which many people are not aware. The study was conducted in Gomma district, Jimma Zone, Oromia National Regional state, Ethiopia, where arabica coffee was first discovered in its natural habitat. Relying on a case study approach, our study uses ethnographic study methods whereby results are presented from the communities’ perspectives and the subsequent discussions with the communities on how the community perspectives could help to better manage coffee ecosystems. Coffee’s utilities and symbolic functions are numerous—food and drink, commodity crop, religious object, communication medium, heritage and inheritance. Most of the socio-cultural services are not widely known, and hence are not part of the benefits accounting of coffee systems. Understanding and including such socio-cultural benefits into the wider benefits of coffee systems could help in promoting improved management of the Ethiopian coffee forests that are the natural gene pools of this highly valuable crop.